Femicide in partnership relations - Spasić Danijela; Kolarević Dag; Luković Zoran (Temida)
In numerous studies in the world, the existence of femicide as a specific form of homicide has been confirmed, indicating its conditions and consequences and the strongest risk factors. The subject of this paper is femicide in intimate partnership, and the aim is to point to the specific characteristics of femicide in intimate parner relationships in Serbia, i.e. to present and analyse the data obtained in the empirical research of this form of murder. The empirical research of femicide in intimate partner relationships in Serbia was conducted in 2016 on the sample of 153 cases of murder of women in the context of intimate partnership, which occurred on the territory of Serbia (without Kosovo and Metohija) in the period from 2001 to 2015. The objectives of the research were to determine the existence and identification of risk factors for femicide. The data was collected from the criminal reports filed by the Ministry of Interior of the Republic of Serbia. The findings of the study confirmed the results of other studies in regard prevalence of femicide and the existence of the following risk factors: exposure of women to chronic intimate partner violence, the availability of firearms, the influence of alcohol and psychoactive substances abuse, the presence of psychological disorders and illness and suicidal tendencies of perpetrators. By applying multidimensional scaling in analyzing elements of crime offending the specific position of suicides that occur in certain number of cases after femicide was pointed out. There was a slight tendency of absence of history of violence in cases where perpetrator of femicide committed suicide. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 179045: Razvoj institucionalnih kapaciteta, standarda i procedura za suprotstavljanje organizovanom kriminalu i terorizmu u uslovima međunarodnih integracija]